TRANSLATION TECHNIQUE IN VARIETY OF ARTICLES FROM INDONESIAN TO ENGLISH: A STUDY IN TRANSLATION CLASS - Yeni Noryatin; Esterria Romauli Panjaitan (Ennichi, 2020)
This research aims to analyze the translation technique in variety of articles from Indonesian to English by the fifth semester students 2019/2020 in STBA JIA. The data will be analyzed by the theory of Benny Hoed about technique of translation. This research is a qualitative research with descriptive analysis, which gives more attention on how deep the translation’s knowledge towards the concept which was being learned and how the theory is used to translate the article. The data of the research is the translation of articles which are translated by the students in translation class. The result of the analysis shows that some techniques are used by students such as transposition, modulation, descriptive, and official translation. From the analysis, it is found that basically all the students gradually can translate well after having many translation practices.